Images of the middle classes in Metro Manila - Bautista, Ma. Cynthia Rose Banzon (1999)
Based on a 1997 survey of 966 respondents, this essay provides an overview of the composition of the intermediate classes in Metro Manila. It portrays an upwardly mobile class for whom education and hard work are the most important factors in deciding class position. They are essentially consumers but with much lower levels of income and investments than their counterparts in the region or in advanced capitalist societies. Family-centered and conservative, the group tends to be ambivalent about political issues--a fact that makes their social mobilization for urgent and long-term concerted action a daunting challenge.
Keywords: Middle class -- Metropolitan Manila (Philippines); Middle class families; Social classes